The 1.4 Å resolution structure of Paracoccus pantotrophus pseudoazurin - Najmudin, Shabir (2019)
This work was supported in part by Fundação para a Ciência e a Tecnologia (Lisbon, Portugal) through project grant POCTI/QUI/64638/2006 and individual grant SFRH/BPD/20357/2004 (SN). The authors would like to thank Dr Cecilia Bonifacio for help with crystallization and Dr Jose Trincao for help with data collection.